Cardiac Ventricular Laceration Due to Child Abuse: Abusive Ventricular Laceration12. Issue 1 (10th July 2018) - Yarid, Nicole; Brown, Emily C.; Boos, Markus; Otjen, Jeffrey; Metz, James; Jenny, Carole; Feldman, Kenneth W.
Abstract: Traumatic cardiac ventricular ruptures in children are rare. Only a single case of left ventricular rupture due to child abuse has been reported. We report a child who sustained a fatal left ventricular apical rupture. It appeared to have resulted from hydrostatic forces resulting from abusive blunt thoracic injury. That he was being abused was previously missed when he was presented to the emergency department with facial pyoderma. It was not noted that he also had lip and oral mucosal injury, sites not affected by staph toxins. As a result, his underlying, abusive and secondarily infected, facial flow type scald burn was not appreciated. Within a week thereafter his fatal injury occurred, accompanied by extensive and obvious associated abusive injuries. Postmortem high‐detail whole body computed tomography scanning aided the autopsy. Although rare, ventricular rupture from abusive blunt thoracic injury can occur.